2012
DOI: 10.1002/jbm.b.32743
|View full text |Cite
|
Sign up to set email alerts
|

Microencapsulation of 2‐octylcyanoacrylate tissue adhesive for self‐healing acrylic bone cement

Abstract: Here, we report the first phase of developing self-healing acrylic bone cement: the preparation and characterization of polyurethane (PUR) microcapsules containing a medical cyanoacrylate tissue adhesive. Capsules were prepared by interfacial polymerization of a toluene-2,4-diisocyanate-based polyurethane prepolymer with 1,4-butanediol to encapsulate 2-octylcyanoacrylate (OCA). Various capsule characteristics, including: resultant morphology, average size and size distribution, shell thickness, content and rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 47 publications
2
37
0
Order By: Relevance
“…14 toluene-2,4-diisocyanate (TDI)-based PU prepolymer and 1,4-butanediol to encapsulate 2-octylcyanoacrylate (OCA) [104]. The produced microcapsules prepared at agitation rates of 350-1100 rpm had an average diameter ranging from approximately 75 μm to 220 μm.…”
Section: Interfacial Polymerizationmentioning
confidence: 99%
“…14 toluene-2,4-diisocyanate (TDI)-based PU prepolymer and 1,4-butanediol to encapsulate 2-octylcyanoacrylate (OCA) [104]. The produced microcapsules prepared at agitation rates of 350-1100 rpm had an average diameter ranging from approximately 75 μm to 220 μm.…”
Section: Interfacial Polymerizationmentioning
confidence: 99%
“…Brochu et al [27] reported polyurethane (PU) walled microcapsules containing medical cyanoacrylate tissue adhesive for developing self-healing acrylic bone cement. The microcapsules were prepared by interfacial polymerization of toluene-2,4-diisocyanate (TDI)-based PU prepolymer with 1,4-butanediol (BD) to encapsulate 2-octylcyanoacrylate (OCA).…”
Section: Interfacial Polymerizationmentioning
confidence: 99%
“…This approach somewhat mimics a network of blood vessels responsible for healing of damaged tissue [2]. The team of White, Sottos and Moore has reported extensively on a similar strategy where liquid monomer is contained in microcapsules that are distributed at 5-10wt% in polymer matrix [3-10]. Again, capsule rupture by a propagating crack releases monomer into the crack plane where the monomer is exposed to co-embedded catalyst, cures, and heals the crack.…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, PMMA bone cement was an attractive option for the first self-healing biomaterial designed using the matrix repolymerization scheme [9, 12]. Our scheme is to encapsulate the water-reactive healing agent 2-octyl cyanoacrylate (OCA) tissue adhesive, commercially-known as Dermabond™, in polyurethane (PUR) microcapsules, and then disperse the capsules in a matrix of Palacos R PMMA bone cement [10]. This creates a catalyst-free self-healing bone cement system is based on the matrix repolymerization scheme (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation